Extended Abstract: Exploring UltraSPARC T2 Processor Parallel Processing Capabilities in Video Streams - Iparraguirre, Javier (2010)
UltraSPARC T2 is a system on a chip. It contains 8 cores and it is capable of running 64 simultaneous hardware threads. Although it was designed for server workloads with high throughput requirements, we tested the architecture using a visual computing application. In this work we perform image binarization in video streams. We use a serial and a parallel implementation to test the performance of the parallelization. An evaluation of the speedup for several screen resolutions of the same video stream shows that this architecture can also be a good choice for real-time video streaming and processing applications.